2015
DOI: 10.1016/j.medici.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and etiology of midfacial fractures: A study of 799 cases

Abstract: This study revealed that the main cause of midfacial fractures was assault. Male patients, aged 15-34 years, more often sustain midfacial fractures. Preventive health care programs should seek measures in the reduction of aggression and violence in close future involving family, school and community institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 21 publications
5
23
0
3
Order By: Relevance
“…3,11-13 A retrospective study from Lithuania observed interpersonal violence among patients with ages between 15 and 34 years to be the predominant cause of facial fractures in their population. 3 Zaleckas et al remarked on the increased incidence of facial trauma between April and October, on weekends and at night. In addition, 14% of patients were found to be under the influence of alcohol during the event.…”
Section: Discussionmentioning
confidence: 99%
“…3,11-13 A retrospective study from Lithuania observed interpersonal violence among patients with ages between 15 and 34 years to be the predominant cause of facial fractures in their population. 3 Zaleckas et al remarked on the increased incidence of facial trauma between April and October, on weekends and at night. In addition, 14% of patients were found to be under the influence of alcohol during the event.…”
Section: Discussionmentioning
confidence: 99%
“…Mean age of our study shows that the patients in third decade of life are the most affected age groups as some earlier reports in the last decade on midfacial fractures also show the patient of third decade of life with the mean of 33.16 ± 14.0 years. 2,8,9 A Road traffic accident being the most frequent cause of midface fractures is reported by several studies. 1,5,6 Present study supports the findings of these earlier studies showing that road traffic accidents represents 57.8% of all etiological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies on midface fractures also showed the high percentage of zygomatic bone involvement. 2,10,11…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations